Music Therapy with Women with Addictions - Gardstrom, Susan C. (Barcelona Publishers, 2021)
Music Therapy with Women with Addictions is designed to provide music therapy students and clinicians with an intimate glimpse into the lives of various women with addictions, illuminating the challenges they bring to music therapy, the strengths and resilience they demonstrate, the resources they build and access during the treatment process, and the transformations they undergo. In doing so, the text is intended to counteract the fear, repugnance, and other adverse emotions that often orbit around individuals with addictions, and instead communicate respect. Rooted in the clinical experience.